2022
DOI: 10.1386/jdmp_00035_1
|View full text |Cite
|
Sign up to set email alerts
|

Is heavy binge-watching a socially driven behaviour? Exploring differences between heavy, regular and non-binge-watchers

Abstract: Results of an online survey suggest that heavy binge-watching of serialized video content might be in part socially motivated. Among a sample of US college students, heavy binge-watchers were more likely to be opinion leaders and to experience fear of missing out (FOMO) than regular binge-watchers or nonbinge-watchers. They also reported higher levels of parasocial engagement with the shows’ characters than other viewers. Contrary to common beliefs, heavy binge-watching did not come at the cost of decreased so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 35 publications
1
15
1
Order By: Relevance
“…The use of substances or excessive forms of behavior to regulate affective states is characteristic of all addictions (Nikmanesh et al, 2014;Mascia et al, 2020). Research has shown that in the case of behavioral addictions, the most common symptoms of abstinence are emotional tension, mood changes, the need for stimulation and craving, and Fear of missing out (FOMO) (Billieux et al, 2015;Anghelcev et al, 2020;Fernandez et al, 2020). Emotional reactions are also associated with distress when binge-watching is blocked.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The use of substances or excessive forms of behavior to regulate affective states is characteristic of all addictions (Nikmanesh et al, 2014;Mascia et al, 2020). Research has shown that in the case of behavioral addictions, the most common symptoms of abstinence are emotional tension, mood changes, the need for stimulation and craving, and Fear of missing out (FOMO) (Billieux et al, 2015;Anghelcev et al, 2020;Fernandez et al, 2020). Emotional reactions are also associated with distress when binge-watching is blocked.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, research has shown that the anxiety-depressive syndrome is associated with a greater frequency of loss of control over binge-watching behaviors and neglect of duties. At this point, it is worth mentioning that problems with selfcontrol and neglect of duties are characteristic of a low level of conscientiousness, which in turn is characteristic of individuals exhibiting excessive binge-watching behavior (Govaert, 2014;Chambliss et al, 2017;Tóth-Király et al, 2017;Anghelcev et al, 2020). An individual escapes from negative emotional states by watching TV series.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations